Crystalline properties of polylactide acid-filled aragonite CaCO3 derived from polymesoda bengalensis (lokan) shell - Damia, M.I.; Amalina, M.A.; Mahshuri, Y. (Maney Publishing, 2014)
Polylactic acid filled with aragonite calcium carbonate composites was prepared using the open mould casting technique. The aragonites used were synthesized from Polymesoda bengalensis shell, locally known as lokan. The crystalline properties of polylactic acid/aragonite composites were measured using a differential scanning calorimeter, to identify the influence of aragonite particle content on the crystalline properties. The result has shown that crystalline onset temperature was obviously higher than those of unfilled polylactic acid resin when the filler content (phi f) was 2 wt-%, then the value varied slightly. For crystalline temperature, the values were slightly varied between filled and unfilled polylactic acid resin. The addition of aragonite also lowered the degree of crystallinity and enthalpy of fusion compared with unfilled polylactic acid resin with the minimum value shown at 8 wt-% filler content (phi f). The result was also supported by X-ray diffraction where the highest polylactic acid peak was shown in unfilled polylactic acid resin and the lowest polylactic acid peak was shown in 8 wt-% filler content (phi f). From the result, it can be seen that aragonite may play the role of a nucleating agent in the polylactide acid matrix resulting in the increase of onset temperature; however, limited movement of the polylactic acid molecular chain and the decrease in the number of molecular chains play a more substantial role to the degree of crystallinity of the composite resulting in the drop of degree of crystallinity and enthalpy of fusion of the composite. The decrease in porosity of the polylactic acid matrix with the inclusion of aragonite also contributed to the drop of degree of crystallinity and enthalpy of fusion of the composite.